Literasi Digital Dalam Kehidupan Masyarakat di Sulawesi Utara - Lady Grace Jane Giroth; Fernando Dotulong; Riani Senduk; Piet Hein Pusung; Only Yonathan Tumiwa; Yobert Kenzhu Taroreh (Puslitbang Akademi Relawan TIK Indonesia (ARTIKA), 2023)
The ability of people to identify, comprehend, and accept the usage of digital technology is essential in this day and age of pervasive digitalization. Digital literacy is crucial to society, particularly in the North Sulawesi Province's educational system. The Importance of Digital Literacy to the North Sulawesi society was conducted by North Sulawesi University of Technology in cooperation with the North Sulawesi Provincial Government and the Ministry of Communication and Information Technology's Directorate of Applications and Informatics. With the help of digital literacy, it is envisaged that members of the public, particularly students, will learn about and be able to utilize the four pillars of digital skills in their daily lives.